Sosialisasi Strategi Pemasaran Digital dalam Meningkatkan Daya Saing UMKM di Desa Sukamukti Kota Banjar - Rubiani, Hani (Sahira Publishing, 2024)
In the current era of industrial revolution 4.0, developments in science and technology greatly facilitate business processes, but on the other hand, they also give rise to intense competition. Digital marketing has become an important tool in increasing business opportunities and reaching wider markets, including in the agricultural sector. In Sukamukti Village, Pataruman District, Banjar City has identified great potential in the agricultural sector. So Usaha Mikro, Kecil dan Menengah (UMKM) in Sukamukti Village only market their products conventionally. UMKM players do not yet understand how to utilize digital marketing strategies to increase competitiveness, for this reason Community Service (PKM) activities are being held by socializing digital marketing strategies to increase competitiveness. The target of this activity is the general public and is specifically aimed at teenagers and UMKM in Sukamukti Village, Pataruman District, Banjar City as partners in this PKM activity. From the results of the questionnaire with an average score of 3.8, it shows that after carrying out this socialization the majority of participants experienced a significant increase in understanding the importance of digital marketing strategies to expand the marketing reach of UMKM in Sukamukti Village, Pataruman District, Banjar City